Co-occurrence Networks do not Support Identification of Biotic Interactions - Peterson, A. Townsend; Soberón, Jorge; Ramsey, Janine; Osorio-Olvera, Luis (Biodiversity Informatics, 2020)
We assess a body of work that has attempted to use co-occurrence networks to infer the existence and type of biotic interactions between species. Although we see considerable interest in the approach as an exploratory tool for understanding patterns of co-occurrence of species, we note and describe numerous problems in the step of inferring biotic interactions from the co-occurrence patterns. These problems are both theoretical and empirical in nature, and limit confidence in inferences about interactions rather severely. We examine a series of examples that demonstrates striking discords between interactions inferred from co-occurrence patterns and previous experimental results and known life-history details.